ORDRE PUBLIC PROTECTION AS LEGITIMATE AIM FOR FREEDOM OF EXPRESSION RESTRICTION IN THE INTERNATIONAL LEGAL ORDER - Ghantous, Marie (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2018)
The right to freedom of expression (FOE) is one of the cornerstones of the rule of law, but it is not an absolute right. It can be restricted on specific conditions. International criminal justice, in its fight against war crimes, and more recently against terrorism, by issuing contempt orders restricting FOE, reveals at first sight a disrespect of this fundamental right. The aim of this paper is to evaluate the legality of the restrictions imposed by international criminal courts, according to the international standards set by international human rights conventions. The applicability of the principles enshrined in the International Covenant on Civil and Political Rights, in particular the restrictive circumstances allowing limitation of FOE before international criminal courts, raises doubts. Restriction of FOE for ordre public protection, in particular, is of great interest. This notion of ordre public appeared in recent international case-law but it is quite difficult to pin down. In an attempt to define the notion of ordre public, this paper made first the distinction between ordre public and neighbouring notions, especially with public policy notion and tried to find out if there was a recognized and identified international public order, and if jus cogens and public order had the same meaning or could be interchanged. Here also, few distinctions with neighbouring notions was conducted in order to answer to the final question which is to know if the administration of justice was part of the international ordre public or a jus cogens norm. As a conclusion, it was found that international human rights conventions are not directly applicable to international criminal courts and that their extension to such sector requires an additional effort from the lawmakers; and that administration of justice was not a peremptory norm of international law; it is not part of the international ordre public and cannot serve as legal ground for FOE restriction.